A phase I study of avelumab, palbociclib, and cetuximab in patients with recurrent or metastatic head and neck squamous cell carcinoma. (December 2022) - Dennis, Michael J.; Sacco, Assuntina G.; Qi, Yuchen; Bykowski, Julie; Pittman, Emily; Chen, Ruifeng; Messer, Karen; Cohen, Ezra E.W.; Gold, Kathryn A.
Highlights: Palbociclib, avelumab, and cetuximab was well tolerated in R/M HNSCC. No unexpected toxicities were observed. Promising response rates were seen (ORR 42%) Abstract: Objectives: We aimed to test the safety of the CDK4/6 inhibitor palbociclib in combination with the EGFR inhibitor cetuximab and the PD-L1 inhibitor avelumab in recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC). Materials and Methods: This phase I study enrolled eligible adult patients with R/M HNSCC into three sequential single dose-escalation cohorts of palbociclib (75, 100, and 125 mg) PO daily on days 1 to 21 of a 28-day cycle in combination with avelumab 10 mg/kg IV every 2 weeks and cetuximab 400 mg/m 2  IV on day 1, then 250 mg/m 2  weekly thereafter. The study followed a 3 + 3 design with no intra-patient escalation. The primary objective was to identify the recommended phase II dose (RP2D); secondary objectives included overall response rate (ORR), duration of response (DOR), progression free survival (PFS), and overall survival (OS). Results: Palbociclib in combination with avelumab and cetuximab was well tolerated, with rash and fatigue being the most common adverse events. A single dose-limiting toxicity was observed at the 125 mg dose of palbociclib: a grade 3 infusion reaction related to cetuximab. The RP2D of palbociclib is 125 mg, with avelumab and cetuximab at standard doses. The ORR by RECIST v1.1 was 42 %, the median DOR and OS have not been reached. Median PFS was 6.5 months. Conclusions: The combination of avelumab, cetuximab, and palbociclib was well tolerated and supports further evaluation in patients with R/M HNSCC. Clinical Trial Registration Number: NCT03498378.